Application of Modern Technical Means of Chemical Reconnaissance and Control for the Detection and Identification of Explosives - V. A. Inozemcev; I. N. Efimov; A. A. Pozvonkov; А. S. Samorodov; V. N. Ponomarev; S. S. Kolbinev (Вестник войск РХБ защиты)
The analysis of the capabilities of modern technical means of chemical reconnaissance and special equipment of chemical control indicates the possibility of quick detection of mined and explosive devices (EDs) by identification of the explosives included in the EDs and related technological impurities. The purpose of this work is to analyze the possibilities of using modern technical means of chemical reconnaissance and control for the detection and identification of explosives. In order to achieve this goal, the authors assessed the analytical characteristics and features of the technical means of chemical reconnaissance and the indication methods implemented in them to determine the possibility of detecting and identifying the components of the EDs. The article shows the possibility of using special military gas detectors operating on the basis of the ion mobility spectrometry (IMS) method to confirm the presence of the vapor phase of explosives. The assessment was carried out on the basis of an analysis of the physicochemical properties of peroxides and nitrogen-containing explosives and a comparison of the achievable concentrations of the vapor phase of nitrogencontaining explosives (TNT, RDX, pentrite, nitroglycerin, dinitrotoluene) with the results of the calculated sensitivity of the IMS method (~10–10 mg/L). It has been established that trace amounts of explosives in liquid and solid states of aggregation can be identified by portable technical means of chemical control, operating on the basis of infrared Fourier spectroscopy and Raman scattering. The ways of expanding the functionality of these technical means by creating specialized databases of spectral data of explosives and accompanying technological impurities are proposed. The inclusion of an additional spectrum bank in the control software of IMS gas detectors must be combined with the implementation of the possibility of program selection of operating modes and database switching by the operator.